Hyaline cartilage formation and tumorigenesis of implanted tissues derived from human induced pluripotent stem cells - Taku Saito; Fumiko Yano; Daisuke Mori; Manabu Kawata; Kazuto Hoshi; Tsuyoshi Takato; Hideki Masaki; Makoto Otsu; Koji Eto; Hiromitsu Nakauchi; Ung‐il Chung; Sakae Tanaka (2015)
Induced pluripotent stem cells (iPSCs) are a promising cell source for cartilage regenerative medicine. Meanwhile, the risk of tumorigenesis should be considered in the clinical application of human iPSCs (hiPSCs). Here, we report in vitro chondrogenic differentiation of hiPSCs and maturation of the differentiated hiPSCs through transplantation into mouse knee joints. Three hiPSC clones showed efficient chondrogenic differentiation using an established protocol for human embryonic stem cells. The differentiated hiPSCs formed hyaline cartilage tissues at 8 weeks after transplantation into the articular cartilage of NOD/SCID mouse knee joints. Although tumors were not observed during the 8 weeks after transplantation, an immature teratoma had developed in one mouse at 16 weeks. In conclusion, hiPSCs are a potent cell source for regeneration of hyaline articular cartilage. However, the risk of tumorigenesis should be managed for clinical application in the future.